Successful Conception In Lean Polycystic Ovarian Syndrome With Ayurvedic Shamana Therapy: A Case Report (The Review of Diabetic Studies, 2025)
Polycystic ovarian syndrome (PCOS) is a leading cause of anovulatory infertility among women of reproductive age. Lean PCOS represents a distinct phenotype that poses diagnostic and therapeutic challenges. This case report describes the successful Ayurvedic management of primary infertility associated with lean PCOS. A 28 year old nulligravida female presented with a four year history of infertility, irregular menstrual cycles of 45–60 days, and scanty menstrual flow. Ultrasonography revealed bilateral polycystic ovarian morphology with increased ovarian volume, and hormonal evaluation showed elevated luteinizing hormone and anti-Müllerian hormone levels. Based on the Rotterdam criteria, the diagnosis of lean PCOS was established. From an Ayurvedic perspective, the condition was correlated with Vandhyatva (infertility) associated with Artavakshaya (oligohypomenorrhea). The patient received Shamana Chikitsa comprising Shatapushpa Churna, Sukumara Kashaya, Drakshasava, and Avipattikara Churna for three months. Gradual normalization of menstrual cycles was observed, followed by spontaneous conception and successful delivery of a healthy infant. This case highlights the potential role of individualized Ayurvedic therapy in restoring reproductive function and improving fertility outcomes in lean PCOS.